A CROSS-SECTIONAL STUDY OF FIXED DRUG ERUPTION OF MALE AND FEMALE GENITALIA AT A TERTIARY CARE HOSPITAL OF MIDDLE GUJARAT, INDIA - Tralsawala, Krunal; BHABHOR, ARTI; OZA, RUTU HARSH; MAKWANA, PRATIK (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Objectives: The point of this study was to introduce a progression of instances of genital lesion with fixed drug eruption, analyze the calprit drug, and distinguish the adjustment of example of medications causing them. Methods: Finding of fixed drug eruption (FDE) was upheld by a positive history and actual assessment. Information including age, site of lesion, time stretch between drug organization, and FDE improvement was gathered and investigated. Results: The most widely recognized causative medication was co-trimoxazole in 34 patients (87.17%), trailed by anti-inflammatory medicine in 2 (5.12%) patients, norfloxacin and erythromycin, each utilized by 1 patient (2.56%). A greatest number of patients had lesions on the glans penis (n=30) (76.92%). Hyperpigmented macular lesion were available in 23 patients (58.97%). The most widely recognized side effects which were introduced by the majority of the patients were pruritus (n=29) (74.35%), trailed by a consuming sensation (n=25) (64.10%). Conclusion: We would like to conclude that co-trimoxazole was the main causative agents of FDE and the most common site was Glans penis in male and in females Vagina and Vulva was the most common site.